(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Inside this work in which it has been planned todemonstrate the state of mind of high school students to environment, evidenceof the disposition of high school studentsin Nigde has been viewed as thesituation matter. This investigation has the qualification of overview modeland procedures of survey and perception have been utilized. The examination hasbeen connected on people getting instruction High Schools in Nigde through 2010to 2011 Education Year. Consistent with the conclusions of the examination; ithas been viewed that the mentality of female understudies are higher inpositive route than male people, the mentality of 10th review learners arehigher in constructive route than 11th review learners, the mentality ofOccupational and General high school studentsare higher in constructive routethan the Anatolian high school students, the demeanor of learners having familythat got instruction at grade school level are higher in constructive routethan others.